2012
DOI: 10.1007/s00259-012-2077-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body FDG PET/CT is more accurate than conventional imaging for staging primary breast cancer patients

Abstract: Full-dose, intravenous contrast-enhanced FDG PET/CT was more accurate than conventional imaging for initial breast cancer staging due to the higher detection rate of metastases and synchronous tumours, although the study had several limitations including a retrospective design, a possible selection bias and a relevant false-positive rate for the detection of axillary lymph node metastases. FDG PET/CT resulted in a change of treatment in a substantial proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 42 publications
1
46
0
9
Order By: Relevance
“…35 Evidence level IV, weak recommendation. 14,20,[36][37][38][39][40][41][42][43][44][45][46] For more detailed information, see Table 7. Question (d): Do 18F-FDG PET/CT findings result in a significant change in therapeutic management?…”
Section: Resultsmentioning
confidence: 99%
“…35 Evidence level IV, weak recommendation. 14,20,[36][37][38][39][40][41][42][43][44][45][46] For more detailed information, see Table 7. Question (d): Do 18F-FDG PET/CT findings result in a significant change in therapeutic management?…”
Section: Resultsmentioning
confidence: 99%
“…Other clinical evidence also showed that PET was more competitive than BS for esophagus, thyroid, nasopharyngeal and lung cancer (Kato et al, 2005;Shinji et al, 2007;Liu et al, 2010;Chang et al, 2013), just as our data shown. BS and SPECT identify osteoblastic responses while 18 F-FDG uptake detecting by PET is related to increase intratumoural glycosis (Masi et al, 2001;Riegger et al, 2012). 18 F-FDG PET should have better sensitivity and specificity than SPECT or BS because by imaging tumor metabolism directly with 18 F-FDG, detection may occur earlier than abnormal 99mTc-MDP accumulation, required for an identifiable bone reaction (Zaman et al, 2011;Lagaru et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Riegger and colleagues reported on 106 breast cancer patients who received FDG-PET/CT and conventional imaging [ 51 ]. In 13 % of the cases, PET/CT detected synchronous tumors, nodal metastasis, or distant metastases not seen with conventional imaging (Fig.…”
Section: Petmentioning
confidence: 93%
“…FDG-PET/CT has been suggested to be more accurate for staging breast cancer than conventional imaging modalities such as plain chest radiography, bone scintigraphy, and axillary and liver ultrasound [ 51 ]. Riegger and colleagues reported on 106 breast cancer patients who received FDG-PET/CT and conventional imaging [ 51 ].…”
Section: Petmentioning
confidence: 98%